2019
DOI: 10.2134/cftm2019.02.0015
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Row Production System for Soybeans in Mississippi Delta

Abstract: The majority of irrigated soybean [Glycine max (L.) Merr.] in Mississippi are planted on raised beds spaced 38 to 40 inches apart. Recently, there has been an increased interest in planting soybean in narrower rows due to multiple potential benefits including increased light interception, improved weed control, and greater yield potential. Field studies were conducted at Stoneville, MS in 2016 and 2017 and at Hollandale, MS in 2016 to evaluate the effects of row spacing and seeding rates on irrigated soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The higher LAI measured under TR planting geometry could have been due to improved interception of PAR that enhanced photosynthesis and biomass accumulation, resulting in significant improvement in seed yield production (17.3% in 2018 and 10.9% in 2019) over the SR geometry. It was reported that an early canopy closure in TR and higher interception of PAR led to greater CO 2 fixation, and the accumulation of photosynthates in the pods resulted in higher seed yield (Smith et al., 2019b). In this study, we expect that early canopy closure under the TR system suppressed mid‐season weed‐seed germination and establishment (data not collected), which helped boost crop growth resulting in better yield returns.…”
Section: Resultsmentioning
confidence: 99%
“…The higher LAI measured under TR planting geometry could have been due to improved interception of PAR that enhanced photosynthesis and biomass accumulation, resulting in significant improvement in seed yield production (17.3% in 2018 and 10.9% in 2019) over the SR geometry. It was reported that an early canopy closure in TR and higher interception of PAR led to greater CO 2 fixation, and the accumulation of photosynthates in the pods resulted in higher seed yield (Smith et al., 2019b). In this study, we expect that early canopy closure under the TR system suppressed mid‐season weed‐seed germination and establishment (data not collected), which helped boost crop growth resulting in better yield returns.…”
Section: Resultsmentioning
confidence: 99%
“…The planter was set to achieve an overall plant population density of approximately 336,000 plants ha −1 . Currently, the Mississippi State University recommends a seeding rate of 345,800 seeds ha −1 for an MG IV soybean planted in April to May on clay soil [20]. Achieved plant populations were estimated at harvest by counting plants in 1 m 2 area in the two center rows at three randomly selected locations in each plot.…”
Section: Methodsmentioning
confidence: 99%
“…Smith, Kaur, Orlowski, Sing, et al. (2019) reported improved TR profitability of $39–188 ha −1 for soybean.…”
Section: Introductionmentioning
confidence: 99%
“…The TR planting employs the same bed spacing as SR with the same number of seeds planted in two rows spaced between 18 and 38 cm on the same bed (Smith, Kaur, Orlowski, Mahaffey, et al., 2019). The evidence in the agronomic literature indicates that TR planting has the potential to improve profits for cotton and soybean production (Pinnamaneni, Annapalli, Reddy, & Fisher, 2020; Pinnamaneni, Anapalli, Reddy, Fisher, & Quintana‐Ashwell, 2020; Smith, Kaur, Orlowski, Mahaffey, et al, 2019; Smith, Kaur, Orlowski, Singh, et al., 2019; I. Stephenson et al., 2011). Although TR‐planted soybean can increase yields by as much as 23% (Bruns, 2011a, 2011b; Grichar, 2007), the evidence is not conclusive that TR planting in cotton results in consistent yield increases (Boykin & Reddy, 2010; Pettigrew, 2015; Reddy & Boykin, 2010; Reddy et al., 2009; D. Stephenson & Brecke, 2010; I. Stephenson et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation